Local Wisdom Values of Maritime Community in Preserving Marine Resources in Indonesia - Sem Touwe (Journal of Maritime Studies and National Integration, 2020)
This study identifies and describes the local wisdom carried out by the coastal communities, especially the people of North Seram, Maluku in preserving the island and marine environment as well as the customary institutions in determining and guarding local wisdom of coastal communities to manage marine resources. The marine resource is started to weaken along with the development of modern technology. This paper provides contemporary phenomena regarding the weakness of customary laws and traditional institutions that regulate marine resources, including social values in the form of rituals, representing the relationship between humans and their environment. The protection of marine resources around them will be an important discussion to see the role of government and society in preserving marine and coastal resources. This study used a qualitative approach to produce descriptive explanations from reports, book reviews, and documents that describe theories and information of both past and present. The result is that the local wisdom maintained as superior cultural practices that are beneficial to human survival, especially in maintaining the sustainability and balance between humans and living objects.